Pemikiran Pendidikan Islam Hamka dengan Pendekatan Historis - Muhammad Nazir Putra; Khoruddin Nasution (Jurnal Pendidikan Islam, 2022)
Inequality in values "‹"‹and morals needs to be overcome through Islamic education so that Buya Hamka's perspective on Islamic education can be applied to the world of education. The world of education today is more oriented to the realm of ta'līm and tarbiyah, and puts aside the realm of ta'dīb, so that it indirectly leads people to a materialistic understanding. Thus, the purpose of this study is to find out what the concept of Islamic education thought according to Buya Hamka in 1950-1980, so that it can be applied to the world of education today so that the inequality of values "‹"‹and morals can be corrected. This research is a qualitative research with library research method. The data obtained refers to written data sources, in the form of books, manuscripts, articles and documents relevant to the research. The research was conducted with a historical philosophical approach using a synchronic theory approach. Furthermore, the analysis method is carried out using a qualitative analysis method approach with the results of a synchronization between Buya Hamka's Islamic Education thoughts and current Islamic education. The results show that the relevance of the concept of Islamic education thought according to Buya Hamka in 1950-1980 with the world of contemporary education, namely in the context of growing and strengthening the individual personality as an alternative solution in the midst of various educational inequality problems that occur where the root of the problem is caused by personal weakness.